Integrating Accounting and Public Health for Water Governance in Fragile States: Mengintegrasikan Akuntansi dan Kesehatan Masyarakat untuk Tata Kelola Air di Negara-negara yang Rapuh - Alqudhayeb, Nael Jaafar Ali (Indonesian Journal on Health Science and Medicine, 2025)
Background: Water governance in fragile states remains a persistent and multifaceted challenge, driven by political instability, weak institutional capacity, and limited integration of environmental and public health data. Objectives: This study synthesizes prior research on Blue Accounting, Material Flow Cost Accounting (MFCA), and Activity-Based Costing (ABC), aiming to develop a multidimensional framework that supports integrated water resource management in fragile contexts. Methods: To carry out this study, I have chosen a qualitative and exploratory design that uses a comprehensive review of literature from 2020 to 2025. The plan is to bring together Blue Accounting, Material Flow Cost Accounting, and Activity-Based Costing with public health indicators for Iraq, which is a fragile state. The researchers used academic research to highlight similarities, notice gaps, and design a model for managing environmental actions that relies on accounting and environmental science. Results: Blue Accounting has emerged as a transparent tool for linking water-related investments and outcomes across institutions and sectors. MFCA enhances resource-use efficiency by identifying material and energy losses within water systems, while ABC supports cost transparency and accountability across complex service chains. Integrating these cost-based approaches with public health indicators—such as access to safe drinking water and incidence of waterborne diseases—can enable evidence-based policymaking, improve intersectoral coordination, and strengthen resilience in water governance. Conclusion: The proposed conceptual model addresses the institutional and operational challenges facing fragile states and offers practical guidance for sustainable, equitable, and accountable water resource management. Highlight : Integrated Accounting Tools — Combining Blue Accounting, MFCA, and ABC improves water governance by enhancing transparency, efficiency, and accountability in fragile states. Public Health Linkages — Aligning water governance with health indicators such as access to clean water and disease rates enables evidence-based policymaking. Contextual Application — The framework is tailored for fragile states like Iraq, addressing institutional gaps and supporting SDG-aligned water management systems. Keywords : Blue Accounting, MFCA, ABC, Water Governance, Public Health, Fragile States